The viscoelastic characteristics of the asphalt concrete modified with different synthetic waxes using a modified Huet- Sayegh model - Mazurek, Grzegorz (International Conference “Environmental Engineering”, 2017)
The article presents the results of dynamic modulus tests carried on the asphalt concrete (AC16W). The sinusoidal load was applied to the samples in accordance with DTC Y method. The neat bituminous binder (penetra tion grade 35/50) was modified by means two synthetic waxes, coming from the Fischer ropsch raction, with various molecular weights and softening point temperature results (hard and softer). The relaxation phenomenon in terms of changes in complex modulus and phase angle was evaluated using the modified Huet-Sayegh (2S2P1D). Estimated model parameters pointed out that the addition of the synthetic wax with the high (hard wax) and the low (softer wax) molecular weight raised the stiffness of the bituminous binder in relation to the reference bitumen 35/50. The application of the modified Huet-Sayegh model showed that the presence of the synthetic wax in the bitumen significantly affected the stiffness modulus of considered asphalt concretes. Basing analysis on Cole-Cole diagram it was found significant differences in the viscoelastic behaviour between the reference asphalt concrete and the asphalt concretes with synthetic waxes. In contrast, there were no significant differences between viscoelastic properties of tested asphalt concretes modified, used in the experiment, synthetic waxes. Furthermore, the sensitivity to the loading time of asphalt concretes containing both synthetic waxes was marginal.
Keywords: 2S2P1D model; synthetic wax; dynamic test; asphalt concrete; master curve